Symposium 2: COVID-19 Experiences Around the World - Cassim, Shakira (International Journal of Human and Health Sciences (IJHHS), 2022)
The presentation gives an overview of the COVID-19 pandemic in South Africa. It discusses the 1st, 2nd and 3rd waves, including the current new COVID-19 variant B1.1.529 and the 4th predicated wave. It also discusses the South African government's response to the COVID-19 pandemic. Muslims in South Africa make up 3% of South Africa's population of nearly 60 million. It further examines the COVID- 19 statistics in the Muslim community, the Muslim response in the relief efforts, and focusing on the response of the Islamic Medical Association of South Africa (IMASA) in the efforts to combat the virus and improve the survival rates. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S9